Dyslexia, literacy and inclusion : child-centred perspectives - MacBlain, Sean; Long, Louise; Dunn, Jill (Los Angeles ; London ; New Delhi : SAGE Publications, 2015)
Designed to raise standards for children with dyslexia, this guide examines early intervention; pupil voice; working as a team; new literacies; child-centered identification, assessment, and provision; and challenges for the inclusive school.--From publisher description.
Changing experiences in childhood : challenges for the 21st century -- Child-centered literacy pathways : pupils' perspectives -- Meeting the needs of children with dyslexia and developmental literacy difficulties : holistic approaches -- Child-centered approaches to the identification and assessment of dyslexia and developmental literacy difficulties -- Raising literacy standards : perspectives on best practice -- Advancing inclusive cultures for literacy learning in the mainstream primary school -- New literacies in the classroom : forging culturally responsive curricula -- Contemporary challenges : looking to the future.
Includes bibliographical references and index.
Keywords: Dyslexic children -- Education; Literacy; Inclusive education; Dyslexic children -- Education; Inclusive education; Literacy; Inkluderande utbildning; Dyslektiker; Education; Storbritannien